Tacrolimus-associated thrombotic microangiopathy in a lung transplant recipient - Boyer, Nathan Lewis (BMJ Publishing Group, 2013)
A 25-year-old woman with a history of bilateral lung transplant secondary to cystic fibrosis presented with non-specific abdominal complaints and was found to have acute kidney injury, thrombocytopaenia and laboratory findings consistent with a microangiopathic haemolytic anaemia. Her thrombotic microangiopathy (TMA) was attributed to tacrolimus, which was discontinued and replaced with cyclosporine with resolution of her TMA and no subsequent complications. This is the fifth reported case of TMA associated with tacrolimus use in a lung transplant patient, and the third to be successfully managed with cyclosporine substitution. Clinicians must be aware of this uncommon, but likely under-reported complication of tacrolimus therapy in lung transplant recipients. Cyclosporine replacement may be used as a successful therapy to treat tacrolimus-associated TMA without increasing the risk of acute rejection that may be associated with other treatment strategies.